FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR DI KANTOR SAMSAT PARE KABUPATEN KEDIRI JAWA TIMUR TAHUN 2024 - Febriana, Lutfia Ariska; Zaman, Badrus; Kurniawan, Andy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
Motor vehicle tax is one of the main sources of regional income and this research aims to determine the factors that influence taxpayer compliance in making motor vehicle tax (PKB) payments at the Pare Samsat Office, Kediri Regency. The method used in this research is quantitative causality. The population used is all taxpayers registered at the Pare Samsat Office, Kediri Regency. The number of samples in this research was 100 respondents with sample determination using the probability sampling method and the technique used was simple random sampling. The data analysis technique used in this research is multiple linear regression analysis using the IBM SPSS Statistics version 23 program. The results of this research show that taxpayer awareness, tax service quality, and tax facilities influence motor vehicle taxpayer compliance. Meanwhile, taxpayer knowledge and tax sanctions have no effect on motor vehicle taxpayer compliance. Based on the results, the conclusion shows that the higher the level of taxpayer awareness, the better the quality of services and tax facilities provided can increase the ratio of taxpayer compliance with motor vehicle tax payments.